The Impact of the Jigsaw Cooperative Learning Model on Discipline and English Learning Achievement in SMPN Students - Srirahayu Ningsih Nuning (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
The purpose of this study was to determine the students' overall Learning Discipline and English Language Learning Outcomes. The role of Language Learning teachers in using the jigsaw type cooperative learning model shows the importance of real context according to the situation in the environment by the students themselves in identifying problems in learning so that the concepts received by students are more meaningful. This research is in the form of a quantitative experiment with the research subjects of Jember Junior High School students. The data in this study are quantitative data obtained from tests of students' knowledge and understanding through questionnaire tests. The results of the percentage of success of this study showed: (1) the effect of the jigsaw type cooperative learning model on improving student learning discipline was 79.0%, (2) the effect of the jigsaw type cooperative learning model on improving student learning outcomes was 81.9%, and (3) the effect of the jigsaw type cooperative learning model on improving student learning discipline and student learning outcomes together was 89.3%. This means that the application of the jigsaw type cooperative learning model in improving students' learning discipline and cognitive learning outcomes has a significant effect